Regulation of the indoleamines by sex steroids - Awah, Edmund Kpabi (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1992)
Alteration of serum tryptophan leads to parallel alterations in brain tryptophan levels. Such changes in brain tryptophan levels has been shown to lead to mood disturbances. The primary enzyme responsible for altering serum tryptophan levels is the liver cytosolic enzyme, tryptophan pyrrolase. Activation of this enzyme is responsible for the enhanced catabolism of circulating tryptophan. The purpose of the present study was firstly to establish whether there is a link between sex steroids and tryptophan pyrrolase activity especially since sex steroids are also known to cause mood disturbances and secondly to determine the effects of sex steroids on brain indolamine metabolism. The results show that all three sex steroids induce the activity of tryptophan pyrrolase implying that they decrease serum tryptophan levels by the activation of tryptophan pyrrolase, thus making less tryptophan available for uptake by the brain. It was also shown that the sex steroids enhance the uptake of Â¹â ´C-tryptophan by brain synatopsomes. In addition, the sex steroids influenced the pattern of metabolism of serotonin by organ cultures of rat pineal glands. It is possible that the sex steroids regulate the availability and uptake of indoleamines in the brain.
Keywords: Steroids -- Research; Steroid drugs -- Research